1992
DOI: 10.1016/0022-2828(92)93088-2
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial glutathione depletion impairs recovery of isolated blood-perfused hearts after global ischaemia

Abstract: This study was performed to determine whether depletion of myocardial glutathione would impair recovery of left ventricular function of blood-perfused, isolated hearts after reversible ischaemic injury. Cats were treated with either vehicle or buthionine sulfoximine (BSO), an inhibitor of gamma-glutamylcysteine synthetase, the rate-limiting enzyme in the synthesis of glutathione. The feline isolated hearts were perfused with the blood of normal donor cats before and after 40 min of global myocardial ischaemia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…In contrast, it is commonly shown that glutathione depletion aggravates post-ischaemic contractile dysfunction (Werns et al, 1992;Blaustein et al, 1989) -consistent with our data in MLP exposed rats. The same result has been seen in blood-perfused (Werns et al, 1992) and intact heart models (Leichtweis and Ji, 2001). Treating both CON and MLP offspring with NAC prior to DEM administration did not nullify the effects of DEM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, it is commonly shown that glutathione depletion aggravates post-ischaemic contractile dysfunction (Werns et al, 1992;Blaustein et al, 1989) -consistent with our data in MLP exposed rats. The same result has been seen in blood-perfused (Werns et al, 1992) and intact heart models (Leichtweis and Ji, 2001). Treating both CON and MLP offspring with NAC prior to DEM administration did not nullify the effects of DEM.…”
Section: Discussionsupporting
confidence: 91%
“…A burst of free radicals on reperfusion is thought to contribute to post-ischaemic contractile dysfunction (Bolli et al, 1989). Glutathione plays a key role in natural antioxidant defence capabilities of the heart and may be critical in determining responses to IR (Forman et al, 1988;Werns et al, 1992). The cellular recycling of glutathione is perturbed in offspring of rats fed with a low protein diet in pregnancy (Langley-Evans et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Impaired diastolic and contractile function in G6PD def hearts is similar to the cardiac dysfunction that has previously been shown to occur during ischemia-reperfusion with depletion of cellular glutathione [7][8][9] or with inhibition of glutathione cycling. 32,33 This suggests that G6PD mediates susceptibility to ischemia-reperfusion injury through maintenance of cellular glutathione and protection against oxidative stress.…”
Section: Depletion Of Cellular Glutathione In G6pd Def Mice During Issupporting
confidence: 59%
“…5,6 GSH allows for the conversion of deleterious hydrogen peroxide and lipid peroxides to water and alcohols, respectively. 6 Depletion of cardiac GSH exacerbates myocardial ischemia-reperfusion injury, [7][8][9] whereas exogenous supplementation with GSH protects against such injury. 7,10,11 Generation of GSH from its oxidized form, GSSG, and subsequent maintenance of intracellular GSH pools require reducing equivalents in the form of the pyridine nucleotide NADPH.…”
mentioning
confidence: 99%
“…Impaired mitochondrial function also leads to the accumulation of deleterious metabolites (NADH, ADP, lactate and H + ), and the depletion of redox-defense antioxidant scavengers glutathione (GSH) [56], both of which can aggravate cellular damage caused by increased oxidative stress.…”
Section: Mitochondrial Energetics and Ros Productionmentioning
confidence: 99%